Exploring Post-Harvest Processing of Tropical Crops: Moringa oleifera and Zea mays as Alternative Ingredients for Gluten-Free Pasta Production - Leal, Imelda; Garlit, Grace B.; Ramos, Lovelyn M.; Baldoz, Daniel J. (Department of Agronomy and Horticulture, IPB University, 2025)
This study examines the potential of Moringa oleifera (moringa) and Zea mays (corn), two tropical crops, as alternative ingredients for gluten-free pasta, with a focus on their post-harvest processing to enhance their utility in gluten-free pasta production. Moringa leaves were carefully dried and ground into a fine powder, preserving their nutritional content, and incorporated into the dough. Corn kernels were milled into flour and blended with moringa powder, resulting in a smooth texture and mild flavor. These postharvest processing methods ensure that both crops maintain their nutritional value, offering significant potential as gluten substitutes and improving the overall quality of gluten-free products. Sensory assessments were also performed to evaluate the acceptability of the pasta. Raw and cooked pasta samples were presented to 100 respondents from five barangays in Banaybanay, Davao Oriental, Philippines. Feedback was gathered on sensory characteristics, including taste, flavor, aroma, and appearance, providing valuable data on the market acceptability of these tropical crop-based, gluten-free pasta alternatives. The gluten-free pasta received high mean scores for all sensory attributes, indicating strong consumer acceptance. The product exhibits promising market potential in the gluten-free food sector, boasting exceptional ratings for taste, flavor, smell, color, and appearance, as well as a general acceptability score of 8.53. The findings highlight the importance of postharvest processing in maximizing the nutritional benefits of moringa and corn, showcasing their potential as sustainable, nutritious ingredients for gluten-free pasta. This recommendation is based on the exceptional nutritional value, safety, and ability to leverage the rich potential of tropical crops.